Correlation of Body Mass Index with Blood Pressure in School Going Children Aged 6 To 14 Years in Ramdhuni Municipality of Eastern Nepal - Ray, Nabal Kishor; Rimal, Hem Sagar; Rimal, Hem Sagar; Mishra, Rajnish; Singh, Shivani; Yadav, Shailendra Kumar (Birat Journal of Health Sciences, 2023)
Introduction: Children of school age groups in developing countries are facing the problem of overweight and obesity. Childhood obesity continues as obesity in adulthood. The chance of high blood pressure (BP) in overweight and obese children is more than healthy weight children. However, in Nepal, data on the relationship between hypertension and obesity, and disease burden in children at the national level are limited. To overcome these diseases and to develop effective prevention strategies, knowing the prevalence of the disease is a priority. Thus, this study aims to determine the prevalence and the relationship between overweight/obesity with BP in school going children aged 6-14 years, living in Ramdhuni municipality of eastern Nepal.Objective:  To find prevalence and the association of BMI with blood pressure in school going children aged 6 to 14 years in Ramdhuni municipality of eastern Nepal.Methodology: This was a school based cross-sectional prospective study conducted at various schools in Ramdhuni municipality from February -March 2022.  A total of 490 apparently healthy students of age group 6-14 years of both boys and girls were enrolled. Measurement of height and weight was done by standard procedure. The data was entered into Microsoft offices excel and analyzed using a statistical package for social sciences (SPSS 20.0).Results: In this present study, data of 490 students aged between 6 and 14 years were evaluated. Of them, 77.8% (n=381) were normal weight, 10.6% (n=52) were overweight and 5.9% (n=29) were obese. The prevalence of hypertension and prehypertension was 0.8% (n=4) and 0.6% (n=3), respectively. The body mass index was statistically significant as an explanatory variable of hypertension for both genders.Conclusion: This study concludes that overweight and obese children are at a significantly higher risk for hypertension than are normal weight children. Blood pressure measurement should be routine and frequent in children, especially overweight and obese children.